Temporal dynamics of SARS-CoV-2 detection in wastewater and population infection trends in Mexico City - Miguel Atl Silva-Magaña; Miguel Atl Silva-Magaña; Marisa Mazari-Hiriart; Adalberto Noyola; Ana C. Espinosa-García; Guillermo de Anda-Jáuregui; Guillermo de Anda-Jáuregui; Enrique Hernández-Lemus (Frontiers in Public Health)
Wastewater-based epidemiology (WBE) provides a non-invasive, community-level approach to monitor infectious diseases such as COVID-19. This study investigated the temporal relationship between SARS-CoV-2 RNA levels in wastewater and reported COVID-19 cases in adjacent populations in Mexico City. A total of 40 samples were collected from the Copilco neighborhood during two epidemiological waves (April-September 2021 and November 2021-February 2022). An optimized one-step RT-qPCR protocol targeting the N1 gene achieved 96.7% efficiency with a detection limit of 10 copies/μL. Spatial classification identified three proximity zones based on drainage system topology. Cross-correlation analysis between viral genome copies and confirmed case data revealed a significant temporal lag of 6-8 days. These results support the application of WBE as an early-warning tool to inform public health strategies and anticipate infection trends.